Ciliary Sulcus Diameter Measurements in Normal Adult Filipino Eyes Using Ultrasound Biomicroscopy - Barbara Joy Masna-Hidalgo, MD; Victor B. Lopez, MD; Maria Elizabeth T. Concepcion, MD; Santiago A. B. Sibayan MD, PhD (Philippine Journal of Ophthalmology)
Objective: To measure the ciliary sulcus diameters (CSD) in phakic eyes of adult Filipinos using ultrasound biomicroscopy (UBM).